2012
DOI: 10.1155/2012/298459
|View full text |Cite
|
Sign up to set email alerts
|

Case Control Analyses of Acute Endophthalmitis after Cataract Surgery in South India Associated with Technique, Patient Care, and Socioeconomic Status

Abstract: Purpose. We investigated acute endophthalmitis incidence following cataract surgery vis-a-vis the current technological and postoperative care changes in higher and lower socioeconomic categories of patients in South India. Methods. In a retrospective case control study, we analyzed 62 cases of acute endophthalmitis and 5 controls for each endophthalmitis case from 46,095 cataract surgeries done between years 1993 and 1998. The time period covered the transition of surgical technique and after care. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 27 publications
4
30
1
1
Order By: Relevance
“…In our study, the male predilection and the age range of 48 to 85 years (mean, 72 years) are similar to that reported in other studies from elsewhere [13, 14, 20, 21]. Similarly, the occurrence of hypopyon as a presenting feature in 60% and corneal involvement in 10% of our cases are comparable to 50–85.7% of hypopyon [1, 13, 14, 20, 22] and 4.8–9% of corneal infiltrate previously reported elsewhere [13, 14]. Gupta et al [13] and Kamalarajah et al [2] had reported a presenting VA < 20/200 in the majority (92.75 and 85%, respectively) of the patients which is similar to our study (86.66%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the male predilection and the age range of 48 to 85 years (mean, 72 years) are similar to that reported in other studies from elsewhere [13, 14, 20, 21]. Similarly, the occurrence of hypopyon as a presenting feature in 60% and corneal involvement in 10% of our cases are comparable to 50–85.7% of hypopyon [1, 13, 14, 20, 22] and 4.8–9% of corneal infiltrate previously reported elsewhere [13, 14]. Gupta et al [13] and Kamalarajah et al [2] had reported a presenting VA < 20/200 in the majority (92.75 and 85%, respectively) of the patients which is similar to our study (86.66%).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, posterior capsule rupture shows the higher association with endophthalmitis reported in previous studies [5, 11, 12]. In our study, the male predilection and the age range of 48 to 85 years (mean, 72 years) are similar to that reported in other studies from elsewhere [13, 14, 20, 21]. Similarly, the occurrence of hypopyon as a presenting feature in 60% and corneal involvement in 10% of our cases are comparable to 50–85.7% of hypopyon [1, 13, 14, 20, 22] and 4.8–9% of corneal infiltrate previously reported elsewhere [13, 14].…”
Section: Discussionsupporting
confidence: 91%
“…But the common factor was the symptom of pain in all cases compared to only 25 % patients complaining pain in post-cataract surgery endophthalmitis in the endophthalmitis vitrectomy (EVS) study [7]. The incidence of endophthalmitis at 11.1 % in our study was between other reported incidences in literature (11.4 % and 12 [5,6]-2.5 % and 2.4 % [3,5,6,8,9]), but 158-fold higher than the incidence of endophthalmitis after cataract surgery in our institute (0.07 % culture proven endophthalmitis [10]) and 55-fold higher than penetrating keratoplasty (0.2 %). Other differences included equal distribution of bacterial and fungal infection; but this cannot be concluded emphatically due to small numbers (Table 2).…”
Section: Discussioncontrasting
confidence: 41%
“…We have previously reported the incidence of acute endophthalmitis after cataract surgery in our centers. 11 This was 0.13% for clinical endophthalmitis and 0.07% for culture-proven endophthalmitis. Thus, the incidences of both clinical and culture-proven endophthalmitis in the current study were less than those after cataract surgery.…”
Section: Discussionmentioning
confidence: 95%